2021
DOI: 10.1111/ajps.12628
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Affective Polarization: Disentangling Policy Disagreement from Partisan Identity

Abstract: Democrats and Republicans clearly dislike one another. Yet, scholars debate whether policy disagreement or partisan identity, per se, drives interparty animus. Past studies suggest the relationship between partisanship and interpersonal affect is spurious, driven by inferred policy preferences. We argue, instead, that policy preferences signal partisan identity when the parties' stances on an issue are well-known. Using a nationally representative survey and four preregistered experiments, we disentangle the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 47 publications
2
97
0
Order By: Relevance
“…Here the focus is not necessarily on issues (such as taxes or abortion) or ideology (liberal versus conservative) but rather on affective group evaluations. In principle, one could hold extremely conservative views without hating the Democratic party or vice versa 81 .…”
Section: Types Of Mass Political Polarizationmentioning
confidence: 99%
“…Here the focus is not necessarily on issues (such as taxes or abortion) or ideology (liberal versus conservative) but rather on affective group evaluations. In principle, one could hold extremely conservative views without hating the Democratic party or vice versa 81 .…”
Section: Types Of Mass Political Polarizationmentioning
confidence: 99%
“…According to some, this new form of partisan identification is mostly fueled by emotional attachment/repulsion rather than political ideology and material interests (8,9), although others have, instead, pointed out the policy-based nature of partisan animosity (10), or concluded that both partisan identity and policy disagreement may affect interpersonal affect (11). In this commentary, I first explain the difference between a form of partisan identification that is rooted in political cleavages and material interests and a partisan identity driven by group attachment dynamics, in which the political identity in itself takes primacy over sociodemographic background and related material and symbolic interests.…”
Section: Baldassarri: the Perils Of Affective Polarization: When Partisan Identity Trumps Social Cleavagesmentioning
confidence: 99%
“…These types of studies are related to the expressive function of partisanship (Huddy, Bankert, and Davies 2018), and they connect to identity processes and other group-based motives (Mason and Wronski 2018). These studies rely mainly on the social identity approach, thus suggesting that increasing in-party identification should be positively related to negative evaluations of the out-party but can also relate to other non-party out-groups (Dias and Lelkes 2021;Iyengar and Westwood 2015;Mason 2015;Mason and Wronski 2018). The second strand of research relates to ideological positions.…”
Section: Party Identificationmentioning
confidence: 99%
“…Affective polarization is one of the most debated topics in political science. Since the seminal work of Iyengar, Sood, and Lelkes (2012), hundreds of studies in the US and others countries have focused on its origin (e.g., Dias and Lelkes 2021;Mason 2015;Rogowski and Sutherland 2016;Webster and Abramowitz 2017) and on its social and political consequences, for instance decreased democratic quality and increased interparty conflict (e.g., Abramowitz and Webster 2018;Huddy and Yair 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation